Village-Owned Enterprises (BUM Desa) Management Strategy Towards Sustainable Village Development - Mardiana; Muhammad Helmi Falah; Prihadyanti, Dian (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. The amount of village funds distributed by the government to villages should be accompanied by an excellent performance of the empowerment programme and the improvement of the village economy through Village-Owned Enterprises (BUM Desa). However, many BUM Desa have stopped operating. This study aims to explore the causes of BUM Desa's poor performance using ethnographic research strategy. The results of this study revealed that the cause of BUM Desa's poor performance is that the community prefers BUM Desa that have physical buildings rather than implementing community empowerment-based businesses through modern cultivation and agriculture. In addition, many villages require higher capacity to formulate a vision for sustainable development. Both factors occur due to the low education level of village heads and communities. The weak performance of BUM Desa is exacerbated by the community culture that considers a person's height not based on capacity but age. In many villages, elders are often more dominant in making proposals than the village head, leading to a lack of focus on the direction of village development. BUM Desa performance is currently at the stage of fulfilling fiscal and social accountability but needs to be more effective in delivering empowerment benefits. Keywords: BUM Desa, economic performance, barriers, community empowerment, sustainability, village development Abstrak. Besarnya dana desa yang disalurkan pemerintah ke desa seharusnya dibarengi dengan kinerja yang sangat baik dari program pemberdayaan dan peningkatan ekonomi desa melalui Badan Usaha Milik Desa ( BUM Desa ). Namun banyak BUM Desa yang berhenti beroperasi. Penelitian ini bertujuan untuk mengeksplorasi penyebab buruknya kinerja BUM Desa dengan menggunakan strategi penelitian etnografi. Hasil penelitian ini mengungkapkan bahwa penyebab buruknya kinerja BUM Desa adalah karena masyarakat lebih memilih BUM Desa yang mempunyai bangunan fisik dibandingkan melaksanakan usaha berbasis pemberdayaan masyarakat melalui budidaya dan pertanian modern. Selain itu, banyak desa memerlukan kapasitas yang lebih tinggi untuk merumuskan visi pembangunan berkelanjutan. Kedua faktor tersebut terjadi karena rendahnya tingkat pendidikan kepala desa dan masyarakat. Lemahnya kinerja BUM Desa diperparah dengan budaya masyarakat yang menganggap tinggi badan seseorang bukan berdasarkan kapasitas melainkan usia. Di banyak desa, para tetua seringkali lebih dominan dalam mengajukan usulan dibandingkan kepala desa, sehingga menyebabkan tidak fokusnya arah pembangunan desa. Kinerja BUM Desa saat ini berada pada tahap pemenuhan akuntabilitas fiskal dan sosial namun perlu lebih efektif dalam memberikan manfaat pemberdayaan. Kata kunci : BUM Desa, kinerja perekonomian , hambatan , pemberdayaan masyarakat , keinginan , pembangunan desa